1995
DOI: 10.1002/jbm.820290404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon content on the resistance to localized corrosion of as‐cast cobalt‐based alloys in an aqueous chloride solution

Abstract: The effect of carbon content on the resistance to localized corrosion of ASTM-F75, as-cast cobalt-based alloys, was studied using potentiostatic polarization tests in Ringer's solution. Critical pitting potentials were estimated from the potentiostatic polarization curves and were found to increase with decreasing carbon content. The highest resistance to pitting corrosion observed at low C contents was attributed to a greater chemical and microstructural homogeneity in the as-cast condition. The results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…A problem with enhanced carbide levels is a reduction in corrosion resistance. 25 This may potentially account for the low levels of metal ions observed in patients with the Ultima MOM THA manufactured from wrought CoCrMo with a low carbon content in the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…A problem with enhanced carbide levels is a reduction in corrosion resistance. 25 This may potentially account for the low levels of metal ions observed in patients with the Ultima MOM THA manufactured from wrought CoCrMo with a low carbon content in the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…3 Montero-Ocampa and Rodriguez 4 correlated pitting corrosion to carbon content of the CoCrMo alloy.…”
Section: Introductionmentioning
confidence: 98%
“…Also Wang et al (1999) concluded that wear resistance of the couple as-cast Co-Cr on as-cast Co-Cr alloy was superior to the high carbon wrought on the high carbon wrought couple tested. The effect of carbon content on the corrosion resistance of Co-Cr-Mo ASTM-F75 was studied by Montero-Ocampo and Salinas (1995). They studied alloys containing 0.07, 0.15 and 0.28 wt.% C, within the specifications of the ASTM-F75 standard.…”
Section: Introductionmentioning
confidence: 99%